1978
DOI: 10.1203/00006450-197803000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Chronically Reserpinized Rat as a Possible Model for Cystic Fibrosis. VII. Alterations in the Secretory Response to Cholecystokinin and to Secretin from the Pancreas in Vivo

Abstract: Summary .isoproterenol (8). In the second model, we have demonstratedThe chronically reserpinized rat has been proposed as an animal model for cystic fibrosis on the basis of morphologic and secretory alterations in the submaxillary gland and of abnormalities in pulmonary secretions. In this investigation, the volume and composition of pancreatic juice from reserpine treated rats (0.5 mg/kg/day) have been compared to those of untreated controls after stimulation with purified cholecystokinin (0.1 pg/ kg body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 5 publications
1
25
0
Order By: Relevance
“…However, the effect of reserpine treatment on the output of the pancreatic juice does not appear to be as dramatic as the CF condition. For example, in reserpinized rats a 35% decrease in the p increatic juice was observed when treated animals were compaled with untreated controls during secretin stimulation (16). In these studies on reserpinized rabbits, only a 25% decrease in the output of the pancreatic juice during secretin stimulation was observed ( Table 1).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, the effect of reserpine treatment on the output of the pancreatic juice does not appear to be as dramatic as the CF condition. For example, in reserpinized rats a 35% decrease in the p increatic juice was observed when treated animals were compaled with untreated controls during secretin stimulation (16). In these studies on reserpinized rabbits, only a 25% decrease in the output of the pancreatic juice during secretin stimulation was observed ( Table 1).…”
Section: Discussionmentioning
confidence: 81%
“…In these earlier studies altered secretory responses to CCK, secretin (16) and to other neurohormonal agents which elicit pancreatic function (15) were observed. Upon stimulation with CCK these investigators noted increases in both the concentration and the output of amylase and total protein in the pancreatic juice of fasted reserpine treated rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An animal model for CF developed by the chronic administration of reserpine to rats shows not only morphologic and secretory changes in the salivary glands (16,17,18,19) and pancreas (20), but also alterations in the protein content of pulmonary lavage fluids, involving a significant increase in the total protein content and in the absolute and relative amounts of a low molecular weight glycoprotein, which were also observed in lung lavage samples from patients with CF (28).…”
mentioning
confidence: 97%
“…The finding of abnormal C1-transport in the submandibular salivary gland of reserpine-treated rats is significant for two reasons: 1) The reserpine-treated rat has been used as an experimental animal model for cystic fibrosis on the basis ofwidespread exocrine gland disturbances resembling those of the human disease (13,19,20). Recent evidence has indicated that C1-permeability is abnormal in the sweat gland (15) and airways (16) of patients with cystic fibrosis.…”
Section: Furosemidementioning
confidence: 99%